On Uncertainty Assessment of Fatigue Damage of Propulsion Shaft Under Ice Impact - Purcell, Etienne; Nejad, Amir R.; Valavi, Mostafa; Bekker, Anriëtte (Volume 7: Polar and Arctic Sciences and Technology, 2021)
In this paper, the importance of maintenance of marine propulsion is discussed with specific focus on the use of condition monitoring to inform maintenance schedules. The design requirements of DNV GL for shafts expected to operate in ice infested waters is adapted and a method is proposed to calculate the short-term fatigue damage during ice impacts. This method uses the Palmgren-Miner rule to calculate fatigue damage based on a transient, lumped-mass model simulation of the shaft with ice loads calculated from shaft measurements using inverse methods. Relevant sources of uncertainty in this assessment method are identified and quantified in order to express the short-term fatigue damage in a stochastic form. Sources of uncertainty include uncertainty in the calculation of ice loads, uncertainty of the transient analysis and uncertainty regarding the actual failure of the shaft as predicted by the S-N material curve and the Palmgren-Miner method. Uncertainties that influence the stress history are found to be the greatest contributor to fatigue damage uncertainty. A method is discussed that calculates the remaining useful life of the shaft as a function of short-term fatigue damage and the identified sources of uncertainty. The S.A. Agulhas is used as a case study to quantify the fatigue damage. publishedVersion